The potential of tissue engineering and regenerative medicine - Sha'ban, Munirah (2014)
Currently, there has been a major health crisis in terms of the shortage of organs. Advances in medicine has improved quality of life and enabled us to live longer. However, as we age, the organs tend to fail more. Although advances in modern surgical have made it possible for someone to have diseased/damaged organs/tissues replaced with healthy living or dead donor, there are not enough transplants to go around. Within the last 15 years, the number of patients requiring an organ has doubled while the actual number of transplants has barely increased. Due to this public health crisis, tissue engineering was born as a means to replace diseased tissue with living tissue that is designed and constructed to meet the needs of each individual patient. This multidisciplinary field has been progressing well as more products have made it to the market. The uses of engineered tissues are now ranging from clinical to non-clinical applications. They are no more considered as end products for regenerative medicine, but have also emerged as model tissues for other research fields like cancer research, drug discovery and biorobotics applications. Cartilage is one of the targets for tissue engineering due to its limitation for self-repair. There is strong evidence that cartilage injuries predispose to osteoarthritis when left untreated. Cartilage was the least complicated tissue to engineer since it contains only one cell type namely chondrocyte. Chondrocytes are present at relatively low concentration, only 5% of volume, and there are no blood vessels or nerves. Due to its avascular nature and low cells density, cartilage can be maintained in vitro at relatively low rates of nutrient and oxygen supply since its metabolic needs are low. However, several issues must be resolved in order to grow in vitro functional cartilage using cells, polymer scaffolds and signaling factors. The success of regeneration of functional cartilage substitutes for depends on various biochemical and biomimetic microenvironment factors that are necessary to facilitate cell differentiation. Like any other technologies, the development of tissue engineering is balanced between opportunities and uncertainties, hope and dejection, and risk and benefits. Keeping a balance between religious and ethical perspectives on the scientific expansion of tissue engineering may help to develop its full potential in transforming the way of medical practice in the future.